Professional Competencies and Attitudes of Metal Crafts to strive Context of Space and Harmony of the Local Culture According to the Review of the Management and Workers in the Establishment of the Steel Industry - Praphanphat, Thepnarintra; Samanthong, Kulpawee (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2021)
-